Les revues littéraires : histoire et problématique - Paul Aron (Contextes)
The article proposes an overview of the French-speaking reviews published in Belgium. It shows that the reviews are an essential support of the literary activity of the country. It also indicates some features of their specific role in a weak and relatively little institutionalized literary institution.